THE PRE-SERVICE TEACHERSâ COMMUNICATION ABILITY ANALYSIS AT TEACHER TRAINING AND EDUCATION FACULTY - Lamhot Naibaho (Universitas Kuningan, 2022)
This study is aimed assessing the English pre-service teachersâ communication ability at teacher training and education faculty. It was done at Universitas Kristen Indonesia within 3 months. This study is a quantitative study and the results of the study are reported descriptively to describe the findings obtained. The study involved respondents of 116 students who were taken using the purposive cluster sampling technique. The instrument of the study is a set of questionnaire which was divided in to two parts (demographics and generic skills data). The data was analyzed by inferential statistical analysis. The finding of this study is that there is no significant difference between the level of Communication ability of male and female students, and there is a significant relationship between the level of communication ability and student achievement. Then, it is concluded that the level of confidence in communication ability of education students is at a high level. However, the ability to communicate in English is still at a moderate level that is less satisfactory. Keywords: Pre-service teachers; communication; ability; gender. Â